What is the effect of self-identified HIV activism in willingness to participate in HIV cure-related clinical trials? Results from the ANRS-APSEC study - Marion Fiorentino; Christel Protière; Luis Sagaon-Teyssier; Mohamed Mimi; Lisa Fressard; MichaelP Arnold; Olivier Lambotte; Janine Barbot; Sylvie Fainzang; Laurence Meyer; Cécile Goujard; Marie Préau; et al. (Elsevier, 2019)
Objectives: Enrolling people living with HIV with undetectable viral load into HIV cure-related clinical trials (HCRCT) is challenging. Few data are currently available about the individual factors that influence willingness to participate in HCRCT (WPHCRCT). We hypothesised that WPHCRCT would be more frequent among people living with HIV considering themselves HIV activists. The objective of this study was to investigate the individual characteristics associated with both WPHCRCT and self-identification as an HIV activist. Methods: The study enrolled 195 long-term ART-treated and virologically suppressed people living with HIV, followed-up in 19 French HIV services, 2016-2017. A Bayesian model averaging approach was used to assess correlates of both outcomes i.e. WPHCRCT and self-identified HIV activism. Results: WPHCRCT was reported by 43% of participants and was positively associated with self-identification as an HIV activist (adjusted odds ratio [aOR] 2.90 95% confidence interval [CI] 2.17-3.63], P<0.05) and self-confidence as an HIV positive person (aOR 1.17, 95% CI 0.99-1.35, P<0.1). Self-identified HIV activists (56% of participants) were more likely to have a higher 'relationship with others' score using the post-traumatic growth inventory (aOR 1.10, 95% CI 0.99-1.20, P<0.1), to obtain information about HIV from a greater number of sources (aOR 1.35 [95% CI 1.00-1.68], P<0.1), and to feel greatly affected by mandatory daily treatment (aOR 2.15, 95% CI 1.27-3.03, P<0.1). All associations had relative importance weight>0.75, indicating strong evidence. Conclusions: WPHCRCT is strongly related to HIV activism, and also to positive psychosocial characteristics as a person living with HIV, especially regarding relationships with others. The desire to contribute to the fight against HIV for the sake of the HIV community and society should be taken into account to improve participation in upcoming HCRCT.